The Poetics of Trauma and Hope in Wounded Water by Anabel Torres - Cecilia Castro Lee (Perífrasis. Revista de Literatura, Teoría y Crítica)
Wounded Water / Agua herida (Bogotá 2004) es un libro de poesía bilingüe de la poeta colombiana contemporánea Anabel Torres (1948). Esta obra ofrece un encuentro poético con el trauma o “las pequeñas sacudidas personales” de las que consistía, en esencia, la poesía de Charles Baudelaire para Paul Valery. Torres escribe de su vida cotidiana como mujer, como poeta y como emigrante radicada en Europa durante las últimas dos décadas. Propongo que Wounded Water /Agua herida es poesía de supervivencia, similar a la que Gregory Orr define como “poesía lírica de transformación”. El campo semántico del agua en la poesía de Torres conceptualiza un amplio espectro de ciclos vitales.Wounded Water / Agua herida (Bogotá 2004) is a bilingual book of poetry by contemporary Colombian poet Anabel Torres (1948). This book offers a poetic encounter with the trauma or “minute personal shocks» Paul Valery cites when referring to Baudelaire’s poetry. Torres writes of her everyday existence as a woman, as a poet, and as an emigrant living in Europe for the last two decades or more. I contend that Wounded Water/ Agua herida is poetry of survival, similar to what Gregory Orr defines as “transformational lyric poetry”. The semantic field of water in Torres’s poetry conceptualizes a broad spectrum from birth, death, and rebirth.